The quality and determinants of voluntary disclosures in annual reports of Shari'ah compliant companies in Malaysia - Mohd Ghazali, Nazli Anum (Emerald Group Publishing, 2013)
Purpose – The objective of this study is to investigate the quality of voluntary disclosure practices by Shari’ah compliant companies (ShCCs) in Malaysia. The study also examines factors influencing the quality of voluntary disclosures.